DEVELOPMENT OF TECHNOLOGY OF THE ASSESSMENT OF STABILITY OF AN ENTERPRISE OF THE CHEMICAL COMPLEX - Mikhail N. Pavlenkov; Natalia A. Smirnova (Статистика и экономика)
In article the essence of the author’s concept of structural creation of system of an assessment and forecasting of stability of the enterprise is stated. The main objective of the developed concept consists of aspiration to provide sustainable functioning and enterprise development by monitoring of indicators and providing with information of experts of various levels of management and creation of the monitoring system of indicators of a sustainable development of the enterprise.